Aplicação da sistemática Gemba Kaizen para criação da linha de gavetas no processo de montagem e fiação - Kemper, Rosiclei Neris (2017)
Production is one of the departments in an organization that should work always thinking of reducing costs and eliminating the waste. There are many tools which can be used to improve production, such as: Value Stream Mapping and Kaizen. Market is constantly changing, consequently the production department need to respond quickly to those changes and adapt itself to the new exigencies to serve and satisfy the customer needs. The competition is increasing, therefore the companies must focus on seeking constant process evolution, making it able to compete by offering better prices, deadlines and high quality and safety in its products. This study shows the implementation of the method Kaizen in an area of assembly engineering products, where the proposal is to create a line of extractable drawers.